FNOTEBOOK'S DIGITAL MARKETING STRATEGY IN BUILDING CONSUMER TRUST - Eza aenal aripin; Teddy Maulana Hidayat Sudirman; Titih Nurhaipah (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study examines the social media strategies implemented by FNotebook in building consumer trust in Majalengka Regency. The rapid development of digital communication has encouraged business actors to utilize social media, especially Instagram, as a medium for promotion and interaction with consumers. The purpose of this study is to identify Instagram-based social media strategies used by FNotebook in building consumer trust through content management, customer interaction, and digital communication patterns. This research employed a qualitative descriptive method with data collected through observation, interviews, and documentation. The results show that FNotebook builds consumer trust through consistent content uploads, transparent product information, responsive communication in direct messages and comments, as well as the publication of customer testimonials. These strategies contribute to strengthening brand credibility and creating closer relationships with consumers. It can be concluded that Instagram-based social media strategy plays an important role in building consumer trust and supporting business sustainability in the digital era.